Mendorong Partisipasi Perempuan Dalam Perencanaan Ekonomi Pembangunan Kampung Takengon Barat Kec. Lut Tawar - Isranuddin Harun; Richasanty Septima S; Ira Zulfa (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Women's participation in economic development planning has many significant benefits, namely women's participation in helping to produce policies and women's participation can help overcome gender gaps. Unfortunately, women's participation in village economic development planning is still not optimal. This service aims to encourage women's participation in planning economic development in the village so that village development is more pro-women. The method of devotion used is socialization and discussion. Based on the test results before and after the implementation of the activity, it can be seen that there is a strengthening of understanding of aspects of access, participation, control, and benefits in gender equal and equitable development. In addition, there is also an increase in women's motivation to participate more in village development planning and men's awareness to provide access and opportunities to women so that articipatory, equal and fair development opportunities become greater.